2015
DOI: 10.1007/s11427-015-4897-1
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 λ protein interacts with ADF1 to regulate actin cytoskeleton dynamics in Arabidopsis

Abstract: Actin cytoskeleton dynamics is critical for variety of cellular events including cell elongation, division and morphogenesis, and is tightly regulated by numerous groups of actin binding proteins. However it is not well understood how these actin binding proteins are modulated in a physiological condition by their interaction proteins. In this study, we describe that Arabidopsis 14-3-3  protein interacted with actin depolymerizing factor 1 (ADF1) in plant to regulate F-actin stability and dynamics. Loss of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The clc2-1 clc3-1 mutant shows impaired microtubule arrangement and modified actin architecture in the hypocotyl Microtubules and the actin cytoskeleton play positive roles in regulating hypocotyl elongation by both shaping cells and providing directionality for elongation (Zhao et al, 2015). These observations prompted us to examine the roles of actin cytoskeletons and microtubules in hypocotyl elongation using clc2-1 clc3-1.…”
Section: Loss Of Function Of Clc2 and Clc3 Increases Pif3 Transcription Levels In Hypocotylsmentioning
confidence: 99%
“…The clc2-1 clc3-1 mutant shows impaired microtubule arrangement and modified actin architecture in the hypocotyl Microtubules and the actin cytoskeleton play positive roles in regulating hypocotyl elongation by both shaping cells and providing directionality for elongation (Zhao et al, 2015). These observations prompted us to examine the roles of actin cytoskeletons and microtubules in hypocotyl elongation using clc2-1 clc3-1.…”
Section: Loss Of Function Of Clc2 and Clc3 Increases Pif3 Transcription Levels In Hypocotylsmentioning
confidence: 99%
“…Arabidopsis thaliana 14-3-3λ interacts with AtADF1 and regulates F-actin organization in vivo (Zhao et al 2015 ). However, contrary to what is expected from animal 14-3-3 that stabilizes phosphorylated ADF/cofilin thus suppresses F-actin depolymerizing activity of ADF/cofilin, a knockout mutant of 14-3-3λ exhibited an elongated hypocotyl phenotype, similarly to Atadf1 and Atadf4 .…”
Section: -3-3 Proteinsmentioning
confidence: 99%
“…However, contrary to what is expected from animal 14-3-3 that stabilizes phosphorylated ADF/cofilin thus suppresses F-actin depolymerizing activity of ADF/cofilin, a knockout mutant of 14-3-3λ exhibited an elongated hypocotyl phenotype, similarly to Atadf1 and Atadf4 . Authors also observed that a 14-3-3λ loss-of-mutant increased the phosphorylation level of AtADF1 thus hindered the proper localization of AtADF1 to F-actin (Zhao et al 2015 ). Therefore, the regulatory mechanism of ADF by 14-3-3 may differ between animals and plants.…”
Section: -3-3 Proteinsmentioning
confidence: 99%
“…Yeast two-hybrid experiment further showed that NtWRKY-R1 could interact with the ABP/ADF (Figure 8 ). The ABP/ADF is considered as primary regulatory factor for the reorganization of the actin cytoskeleton (Maciver and Hussey, 2002 ; Zhao et al, 2015 ), which is involved in various cellular and developmental activities (Ketelaar et al, 2004 ; Kandasamy et al, 2007 ), as well as cell signaling in response to biotic and abiotic stresses (Hussey et al, 2002 ). The actin in the nucleus, as a structural protein, participates in the formation of the nuclear skeleton and chromatin skeleton, binds ADF to regulate chromatin structure and gene transcription, mRNA processing and transportation (Burgos-Rivera et al, 2008 ; Zheng et al, 2013 ; Fu et al, 2014 ; Henty-Ridilla et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%